Hemostatic Alterations in Patients With Cirrhosis: From Primary Hemostasis to Fibrinolysis. Issue 6 (30th May 2020) - Zermatten, Maxime G.; Fraga, Montserrat; Moradpour, Darius; Bertaggia Calderara, Debora; Aliotta, Alessandro; Stirnimann, Guido; De Gottardi, Andrea; Alberio, Lorenzo
Abstract : In the setting of liver cirrhosis (LC), profound hemostatic changes occur, which affect primary hemostasis, coagulation, and fibrinolysis. They involve prohemorrhagic and prothrombotic alterations at each of these steps. Patients with cirrhosis exhibit multifactorial thrombocytopenia and in vitro thrombocytopathy, counterbalanced by increased von Willebrand factor. The resultant shift is difficult to assess, but overall these changes probably result in a rebalanced primary hemostasis. Concerning coagulation, the reduced activity of coagulation factors is counterbalanced by an increase in factor VIII (produced by liver sinusoidal endothelial cells), a decrease of the natural anticoagulants, and complex changes, including changes in circulating microparticles, cell‐free DNA, and neutrophil extracellular traps. Overall, these alterations result in a procoagulant state. As for fibrinolysis, increased tissue‐type and urokinase‐type plasminogen activators, a relatively decreased plasminogen activator inhibitor 1, and decreased levels of thrombin‐activatable fibrinolysis inhibitor and α2‐antiplasmin are counterbalanced by decreased plasminogen and a decreased fibrin clot permeability. Whether and how these changes shift fibrinolysis remains to be determined. Overall, the current consensus is that in patients with cirrhosis, the hemostasis is shifted toward a procoagulant state. We review the published evidence for the concept of LC as a prothrombotic state, discuss discordant data, and highlight the impact of the underlying cause of LC on the resultant imbalance.